What is real in hyperrealism? Pictorial representation and layers of the visible (Itinera, 2024)
American hyperrealist painting is one of the most famous phenomena of American culture in general, but also one of the most difficult to fit into the art-historical canon. Hyperrealism causes difficulties in interpretation because it is placed between traditional mimetic painting skills and the imaginary of American popular culture. In this article, we will suggest that hyperrealism may be evaluated as primarily a philosophical problem of the understanding of reality and its transformation into a pictorial surface. We will try to foreground the neglected possibility that the “excess of the real” in a painting can be in some allegorical function: as the opposite of reality, in other words, as an absence rather than a presence. Moreover, we will point out the twofold contingency of the hyperrealist pictures: as a philosophical platform for the study of pictorial representation on the one hand and as an evidence that there is no universal theory of pictorial depiction that would establish a connection between extra-pictorial reality and representation on the other. The article will analyze why hyperrealism as an artistic style is not crucially defined by the problem of mimesis, but rather by the problem of (dis)continuity in regard to reality. Instead of asking why hyperrealist paintings are so close to human perception of the world, we try to unveil consequences of its playing on the edges of complex systems such as representation, depiction, similarity, imagination, simulation and recognition. Referring to the aspects of reality in painting, photography and conceptual art we will consider to what extent theory can influence a seemingly straightforward artistic phenomenon to gain a different kind of relevance, while providing insights into the possibilities of viewing hyperrealist paintings as both part of the cultural imaginary and philosophical objects.
Keywords: hyperrealism, depiction, naturalisation of perception, intensities of reality